2011
DOI: 10.1071/he11027
|View full text |Cite
|
Sign up to set email alerts
|

Culturally appropriate methods for enhancing the participation of Aboriginal Australians in health-promoting programs

Abstract: Four local processes reflected the unique characteristics and profile of each community.They included the need to be responsive to local systems and structures, to incorporate local cultural traditions and knowledge bases, to use locally accepted forms of cultural communication, and to facilitate oca community participation and leadership in the program. Importantly, these factors determined the experience of the program within each community, ultimately influencing its acceptability, effectiveness and sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 9 publications
1
84
0
Order By: Relevance
“…18 Indigenous Australians have reported that gathering and consuming bush foods may help restore and protect culture. 18 In addition, it was thought that the use of bush foods would to some extent foster a return to traditional dietary patterns, which had been disrupted by colonisation and supplanted by poor nutrition influenced by Western culture. 18 Importantly, it was recognised that to sustain behavioural change the use of bush foods needs to be based on local knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Indigenous Australians have reported that gathering and consuming bush foods may help restore and protect culture. 18 In addition, it was thought that the use of bush foods would to some extent foster a return to traditional dietary patterns, which had been disrupted by colonisation and supplanted by poor nutrition influenced by Western culture. 18 Importantly, it was recognised that to sustain behavioural change the use of bush foods needs to be based on local knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, it was thought that the use of bush foods would to some extent foster a return to traditional dietary patterns, which had been disrupted by colonisation and supplanted by poor nutrition influenced by Western culture. 18 Importantly, it was recognised that to sustain behavioural change the use of bush foods needs to be based on local knowledge. 18 Given these benefits, it appears that restoring the widespread use of bush foods could substantially lead to improving the health and wellbeing of Indigenous communities in the Pilbara.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classes were held in a community centre situated on the grounds of the local primary school, which was familiar to the participants, promoting feelings of safety and security (14) . Each cooking class ran for 3-4 h and typically began with a nutrition education session followed by food preparation and cooking.…”
Section: Methodsmentioning
confidence: 99%
“…The word 'Bindjareb' refers to an Aboriginal region within the Nyungar nation of south-west Western Australia and 'yorgas' is the Nyungar word for woman or women. To ensure the success of health promotion initiatives in Indigenous communities, research has shown that programmes must be developed collaboratively with genuine community engagement and must be specific to community needs (14,15) . To this end the four components incorporated in the BYHP were those considered most appropriate by the community Elders and leaders to address the perceived health concerns of their community.…”
mentioning
confidence: 99%